The present and future trends of leadership styles and knowledge hiding through science mapping analysis - Muhammad Ashraf, Fauzi; Umi Nabila, Alias; Tan, Christine Nya-Ling; Wider, Walton; Mukherjee, Subhodeep; Al-Adwan, Ahmad Samed; Udang, Lester Naces (World Scientific Publishing Co Pte Ltd, 2025)
This study investigates the scientific structure of leadership style on employee knowledge-hiding behaviour in organisation. Knowledge hiding is a counterproductive and negative behaviour that diminishes organisational progress and performance. This behaviour primarily occurs due to the type of leadership prevalent in the organisation. Employing a science mapping approach, this study discovers the link between knowledge-hiding behaviour and leadership style using bibliometric analysis. Bibliographic coupling depicts three themes associated with different leadership styles on knowledge hiding (clusters 1 and 2), the relationship between knowledge sharing and knowledge hiding (cluster 3), underpinning theories (cluster 4) and the impact of leadership on employee creativity (cluster 5). The co-word analysis presents future trends associated with transformational leadership on knowledge sharing (cluster 1), knowledge hiding and employee innovation (cluster 2) and the synergy of psychological safety and workplace climate (cluster 3). The findings contribute to the theoretical and managerial implications of mitigating knowledge-hiding behaviour. Scholars and practitioners can intervene by knowing the predictors of knowledge hiding from the leadership style and strategically planning to overcome this obstructing behaviour in the workplace. This review fills in the knowledge sharing–knowledge hiding conundrum gap by exploring the role of leadership as a foundational base for future studies.